Effect of Kombucha Prepared from Green Tea on Blood Glucose Level and Lipid Profile in Diabetic Rats - L Rasouli; H Fallah Huseini; SA Hoseini (Institue of Medicinal Plants, ACECR, 2014)
Background: Diabetes is chronic and progressive disease in which lipid disorder is one of the common disorders which in turn cause the formation of its short-and long-term effects. Objective: This study was aimed to examine effect of Kombucha prepared from green tea on blood glucose and lipid profile in diabetic rats. Methods: In the present study, 30 alloxan-induced diabetic wistar rats randomly divided in to three groups: 1) control group, 2) diabetic group receiving green tea and 3) diabetic group receiving Kombucha prepared from green tea. Experimental diabetes in rats was induced by intraperitoneal injection of Aloxan (130 mg/kg). The animals of groupsgreen tea and Kombucha received respectively green tea and Kombucha (made from green tea) and group1 received water 5 ml/kg by oral gavage daily for four weeks. Then glucose and lipid profile were measured. Results: Compared to control group, Serum glucose levels in groups green tea and kombucha were significantly reduced (respectively p=0.002 and p=0.0001). Compared with green tea, Kambocha decreased glucose significantly (p=0.050). Increasing concentrations of HDL in kombucha group in comparison with green tea group was significant (p=0.02) and reduction of total cholesterol and LDL concentration in groups kombucha and green tea in comparison with control group was significant. Meanwhile, decreased average total cholesterol and LDL concentration in kombucha group in comparison with grean tea group was also significan (respectively p= 0.0001 and p =0. 0001). Conclusion: Use of Kombucha caused a decrease in serum glucose, LDL, total cholesterol and an increase in HDL cholesterolthat this effects are probably because of fermentation process products.